The Effect of Stereotype Threat on Age Differences in Prospective Memory Performance: Differential Effects on Focal Versus Nonfocal Tasks. (9th August 2017) - Zuber, Sascha; Ihle, Andreas; Blum, Anaëlle; Desrichard, Olivier; Kliegel, Matthias
Abstract: Objectives: The current study examined the effects of stereotype threat on prospective memory (PM) performance in younger versus older adults by using a focal (i.e., low cognitive demands) and a nonfocal (i.e., high cognitive demands) PM task. Method: Sixty younger and 60 older adults performed an event-based PM task, in which task instructions were experimentally manipulated. Half of the participants received instructions that emphasized the memory component of the task (memory condition; i.e., high stereotype threat for older adults) whereas the other half was instructed that the task evaluated participants' reading-ability (reading condition; i.e., low stereotype threat). Results: Older adults' PM performance was worse than younger adults' only in the memory condition and these effects were specific for nonfocal PM cues as well as for old-old adults. Discussion: Conceptually, this indicates that stereotype threat particularly impacts age effects for cognitive processes associated with executive control and that this particularly affects old-old adults. Therefore, the current findings illustrate for the first time that age differences in PM can be influenced by stereotype threat and suggest changes in controlled attention as possible cognitive pathway.